Motivational Elements in Computer Games for Learning Mathematics - Juric, Petar; Brkic Bakaric, Marija; Matetic, Maja (International Journal of Emerging Technologies in Learning (iJET), 2021)
One of the main drawbacks of delivering new teaching lessons in e-learning systems is the lack of motivation for using those systems. This paper analyses which elements of computer games for learning mathematics have a beneficial effect on intrinsic motivation and give students continuous feedback in order to improve the learning process. While the control group has access to the basic version of the educational computer game, the experimental group uses the version enriched with additional motivational elements which include enhanced graphics for indulging in the game, messages of support while playing the game, and the possibility to compare results with fellow peers in terms of trophies and medals won.